Pengembangan “Green Squad” Gen Z: Inspirasi dan Aksi Hijau di Era Digital Dukungan “Zero Sampah” di SMP 4 Muhammadiyah Yogyakarta: Indonesia - Utami; Wijayati, Punik Mumpuni; Safitri, Indah (UII, 2026)
Waste management remains a major challenge in various settings, including schools. SMP Muhammadiyah 4 Yogyakarta initiated the Zero Waste Program to foster a sustainable, environmentally friendly culture. This program aims to reduce waste generation, raise student awareness, and establish an integrated waste management system. The program began with a situational analysis to identify the sources and types of waste within the school. Based on these findings, a Zero Waste Team consisting of teachers, students, and external partners—was formed to design and implement the program. The team developed educational modules, provided segregated waste bins, and facilitated workshops and training on the 3R principles (Reduce, Reuse, Recycle) through practical learning activities, such as creating wall magazines from waste materials and reducing the use of single-use products. The program was further strengthened by concrete actions supported by digital campaigns and active student participation as change agents. As part of its sustainability strategy, the program also encouraged intergenerational collaboration by involving students, teachers, and parents. This approach ensured the transfer of knowledge and the long-term continuity of an environmentally conscious culture within the school. Regular monitoring and evaluation were conducted to assess the program’s effectiveness. The results demonstrated the establishment of a sustainable waste management system, a reduction in waste volume, and increased environmental awareness. This study concludes that schools can serve as environmentally friendly models that are replicable in other educational institutions.